2014
DOI: 10.5713/ajas.2014.14216
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Coconut Materials on <i>In vitro</i> Ruminal Methanogenesis and Fermentation Characteristics

Abstract: The objective of this study was to evaluate the in vitro effects of coconut materials on ruminal methanogenesis and fermentation characteristics, in particular their effectiveness for mitigating ruminal methanogenesis. Fistulated Holstein cows were used as the donor of rumen fluid. Coconut materials were added to an in vitro fermentation incubated with rumen fluid-buffer mixture and timothy substrate for 24 h incubation. Total gas production, gas profiles, total volatile fatty acids (tVFAs) and the ruminal met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…However, the adverse impact is dose-dependent and supplementation of 2% silkworm pupae oil per se did not affect the digestibility. The results are in agreement with the previous findings [24,[27][28][29][30], reported a significant reduction in methane production with oil supplementation. Unsaturated fatty acids in silkworm pupae oil could be toxic to the protozoa, as evidenced in the present study with their decreasing numbers.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, the adverse impact is dose-dependent and supplementation of 2% silkworm pupae oil per se did not affect the digestibility. The results are in agreement with the previous findings [24,[27][28][29][30], reported a significant reduction in methane production with oil supplementation. Unsaturated fatty acids in silkworm pupae oil could be toxic to the protozoa, as evidenced in the present study with their decreasing numbers.…”
Section: Discussionsupporting
confidence: 93%
“…However, at higher levels (beyond 2%), the reduction in DMD with a concurrent reduction in rumen protozoa appears to be equally responsible for the reduction of methane production. The results are in accordance with the previous studies, where reported the reduction in the protozoal population with oil supplementation [27,[34][35][36].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…(2015) reported that some plant metabolites especially essential oils have a unique effect of reducing carbohydrate and protein degradation in the rumen by selectively inhibiting the function of some microorganisms. In addition, many researchers have reported various positive influences of plant secondary metabolites on the reduction of methane gas emission produced by ruminants ( Patra and Yu, 2012 , Oskoueian et al., 2013 , Kim et al., 2014 ). Apart from being a global phenomenon, Beauchemin et al.…”
Section: Botanical Extractsmentioning
confidence: 99%
“…Use of plant origin feed additives to mitigate methane emission and to improve the performance of the animals is now been considered as desirable replacement of other feed additives like chemical, antibiotics, nitrate etc because of less risk of toxicity in the animal and no residual effect in animal produce [ 5 10 ]. The use of plant origin additives containing plant secondary metabolites (PSM) have preference in animal feeding because of their natural occurrence [ 11 13 ]. The most commonly tested PSMs are tannins, saponins and essential oils (EOs).…”
Section: Introductionmentioning
confidence: 99%